In vitro activity of Curcuma longa Extract Against the Promastigote Stage of Cutaneous Leishmania Parasite - Faleeha Habeeb Hussien; Alaa H. Al-Charrakh (Medical Journal of Babylon, 2025)
Background: Plants are an excellent source of herbal medicines, and their natural products have antimicrobial potential for the management of numerous diseases, such as leishmaniasis. Objectives: This study investigated the antileishmanial activity of Curcuma longa plant extracts (alcoholic and aqueous extracts) against the promastigote form of cutaneous Leishmania parasite during 9 days of growth, as well as to investigate the effects of metronidazole and cotrimoxazole drugs on promastigote stages in different concentrations. Materials and Methods: To investigate cutaneous Leishmaniasis (CL) parasites in vitro using cultures of parasites. Using 0.5 g/100 mL of C. longa plant extracts (alcoholic and aqueous) as minimum inhibitory concentration poses significant activity on promastigate stages of the CL parasite. Two drugs were used, metronidazole and cotrimoxazole, in concentrations of 7,500 and 10,000 mg/mL. Results: All three extracts of the C. longa plant exhibited antileishmanial activity on promastigate stages of the parasite during 9 days of growth. Curcuma longa plant alcoholic extracts in different concentrations (0.5, 1, 1.5, 2) g/100 mL reduced the growth of promastigate stages of the CL parasite during 9 days. Also at the same concentrations of C. longa aqueous extract (hot water), the growth of promastigate stages was considerably decreased during 9 days. Curcuma longa alcoholic plant extract was found to be most active against promastigate stages of CL compared to aqueous extracts. The two drugs used, metronidazole and cotrimoxazole, at concentrations of 7,500 mg/mL and 10,000 mg/mL), completely killed the promastigate stages of CL by the sixth and fifth day of treatment. Conclusions: Curmeric plant extracts showed inhibitory efficacy toward promastigate stages of cutaneous Leishmania parasite, and therefore used as an alternative treatment against parasites associated with CL.